GATA4 binding to the Sox9 enhancer mXYSRa/Enh13 is critical for testis differentiation in mouse - Yuya Ogawa; Iku Tsuchiya; Shogo Yanai; Takashi Baba; Ken-Ichirou Morohashi; Takehiko Sasaki; Junko Sasaki; Miho Terao; Atsumi Tsuji-Hosokawa; Shuji Takada (Communications Biology)
Abstract In mammals, SOX9/Sox9 expression in embryonic gonads is essential for male gonadal sex determination. Multiple enhancers of Sox9 have been identified, of which the mXYSRa/Enh13 enhancer plays a crucial role in mice. SOX9 and SRY binding sites within the enhancer have been identified as functional. Simultaneous deletion of both sites in mice resulted in male-to-female sex reversal. However, the existence of other critical functional sequences remains unclear. This study identified an additional functional sequence by generating mice with partial deletions in mXYSRa/Enh13. Two nucleotide substitutions within the sequence were sufficient for male-to-female sex reversal. In vivo binding assay by CUT&RUN revealed that GATA4 binds to the sequence. In vitro luciferase assay showed that GATA4 promotes the enhancer activity and the substitution of the sequence reduces the effect. Taken together, the functional sequence in mXYSRa/Enh13 is essential for testis differentiation and requires GATA4 binding.